PEMANFAATAN TEKNIK PENGIDERAAN JAUH UNTUK PEMETAAN TINGKAT KERAWANAN KEBAKARAN PERMUKIMAN (Geo-Image, 2015)
Population growth in semarang city more rapidly with the advent of the economy , settlement , education , and culture .Population growth city and the rate of urbanization cause trouble the availability of room for settlement the limited especially residential for the middle class down .Man need to land settlement and the availability of empty land on large cities more limited has resulted in compaction settlement was .Where these conditions the space between building units almost no , in a residential area of buildings are connected and sticking with each other .Environmental conditions like this not qualify livable especially in terms of safety , comfort , health and environmental danger .The problems could jeopardize settlement safety environment and soul one is the incident.Â Fire incident besides life-threatening also inflict a wound , psychological trauma widespread damage to property , investment loss , impoverish the community , lost their jobs and others .The fire accident was happened also is dangerous one unit of house but it can more than one block settlement .Information about vulnerable to fire on settlement pertaining on the locations and area , hence required a data presentation used to can inform us and distribution of space .Presentation of data this can be poured in a map .A map having the ability that is easy to use , have the impression visual strong and having value for trusted .Thus map can be used as media of communication very fine in relay the information on characteristic of space from embodiment that is in their surroundings . Data processing of satellite images to menetukan potential area vulnerable based on variable certain required a system information i.e. the system geographic information.Data referral spatial that may be analyzed subsequently inform for a certain purpose by processing data, editing data and produce output of a map can molded into hard copy and can be utilized by the user a map ( map user ).